Augmanted Reality Dengan Metode Marker Based Tracking Struktur Dan Fungsi Jaringan Tumbuhan - Hutagalung, Hasan Basri; Lubis, Imran; Aulia, Rachmat (Universitas Harapan Medan, 2024)
Learning the structure and function of plants is done to achieve the basic competencies (KD)studied. Learning the structure and function of plant tissues can be carried out well with aninteresting learning interaction between educators and students. Therefore, there is somethingnew by using Augemented reality (AR) which makes learning more interesting and will fosterthe interest of students. The problems studied by researchers about how the description of theneeds of Augemented reality-based simulations on plant tissue structure and how the validityand practicality of Augemented reality-based simulation media development with Marker-basedtracking method in plant tissue structure lessons. Later with the problems studied by the authorshave a goal that the use of Augemented reality later in simulation media can provide a betterlearning experience that is interesting and interactive for students and students can use mobiledevices or tablets that are commonly used when accessing AR simulations. Analysis of systemproblems that are being researched by the author using software and hardware that helps to work on Augemented reality for new learning for students about learning the structure andfunction of plant tissues that contain 3D information. The results of the research obtained by theauthor can make Augemented reality applications to increase the interest of students bydisplaying 3D images and containing more interesting information to increase students to learnin the future. The conclusion of the research that has been done to increase students' interest inlearning about the structure and function of plant tissue material